2004
DOI: 10.1002/art.20171
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose aspirin and prevention of cranial ischemic complications in giant cell arteritis

Abstract: Objective. Cranial ischemic complications such as cerebrovascular accidents (CVAs) and acute visual loss are among the leading causes of giant cell arteritis (GCA)-related morbidity. In this retrospective study, we evaluated the effect of treatment with low-dose aspirin on the incidence of cranial ischemic complications in GCA.Methods. Charts of 175 consecutive patients in whom GCA was diagnosed between 1980 and 2000 were reviewed for medical data. Data for 166 patients who were followed up for at least 3 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
163
2
20

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(188 citation statements)
references
References 32 publications
3
163
2
20
Order By: Relevance
“…Two recent studies from tertiary care centers have demonstrated that antiplatelet therapy may reduce the risk of cranial ischemic complications in patients with GCA (9,10). The present population-based study did not confirm those results.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Two recent studies from tertiary care centers have demonstrated that antiplatelet therapy may reduce the risk of cranial ischemic complications in patients with GCA (9,10). The present population-based study did not confirm those results.…”
Section: Discussioncontrasting
confidence: 99%
“…Although ischemic damage in GCA is usually attributed to occlusive vasculopathy caused by intimal proliferation, a possible role of thrombosis in causing cranial ischemic complications cannot be excluded (7,8). Low-dose aspirin or anticoagulant therapy has been shown to reduce the risk of visual loss and CVAs in patients with GCA (9,10). The benefits of low-dose aspirin in GCA could derive from the antiplatelet effect of aspirin, although its antiinflammatory action may also be involved (11).…”
mentioning
confidence: 99%
“…Although this finding requires further confirmation in other populations, it is potentially important because it implies that a genetically determined endothelial dysfunction may predispose individuals to this vasculitis. Interestingly, pilot studies have found that low-dose aspirin and the anti-tumor necrosis factor ␣ antibody infliximab may improve the efficacy of corticosteroid treatment of GCA (32,33). In addition, 2 recent studies have demonstrated improved endothelial function using these 2 drugs (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Low-dose aspirin has also been shown to decrease the rate of visual loss and cerebrovascular accidents in GCA. 4 In recurrent or resistant GCA, methotrexate or other immunosuppressives (eg azathioprine or leflunomide) may be used as adjuvant therapy to allow reduction in the cumulative glucocorticosteroid dose, or a higher probability of glucocorticosteroid discontinuation without relapse. 5 …”
Section: Treatment and Complications Of Gcamentioning
confidence: 99%